Teaching of technical disciplines in a mixed format at the university - Ғабдысалық, Риза; Канагат, Толубаева (Pedagogy and Psychology, 2022)
When the whole world switched to distance learning due to the pandemic, the education system also did not stand aside. Distance learning differs significantly from traditional, as practice shows, on-line students and teachers have faced serious problems hindering learning, and in some special disciplines, the level and quality of knowledge has significantly decreased than in traditional training. Among the students of VTU in the Republic of Kazakhstan, an analysis of the development of special disciplines was carried out, the data were summarized by analysis, study and observation. As a result, the academic performance of about 500 students in technical disciplines was analyzed. The results of the analysis were reviewed and discussed at the “Distance Education Application and Research Center (AKUZEM)” of Akdeniz University during the internship and a plan of training in technical disciplines in a mixed format was drawn up. The results obtained in the article showed which form is most effective in the development of a distance learning system related to the teaching of technical disciplines, important and useful information is given to improve the effectiveness of teaching and learning. Our work contributes to education in the context of distance learning by supporting an expanded model of adoption of distance technologies and taking into account differences in culture, learning style and social environment compared to other countries.